Immunohistochemical examination of immunoreactivity of transient receptor potential melastatin 2, glutathione peroxidase 4 and spexin in lichen planus - Celik, Mehmet Semih; Cicek, Demet; Demir, Betul; Kuloglu, Tuncay; Artas, Gokhan; Hancer, Serhat (Springer, 2024)
Backround In this study, we aimed to investigate the potential contributions to the disease by examining the immunoreactivities of SPX in LP-affected skin tissue using immunohistochemical methods, in light of its recent prominence as a molecule related to diabetes mellitus, along with apoptosis and ferroptosis mediated by GPX4 and TRPM2 channels facilitating oxidative stress-induced cell death. Objective This research explored the immunohistochemical expressions of TRPM2, GPX4, and SPX in Lichen Planus (LP) patients compared to healthy individuals. Materials and methodsForty skin samples were collected, split equally between LP patients and healthy controls, excluding those with other conditions. Samples underwent immunohistochemical staining for TRPM2, SPX, and GPX4, using secondary antibodies and chromogens AEC or DAB. Histoscores were calculated based on staining diffusiveness and severity. Statistical analyses were performed with SPSS 22.0, using t-tests and ANOVA, with significance set at p < 0.05. Results There were no demographic differences between groups (p > 0.05). LP patients showed significantly lower TRPM2 and GPX4 histoscores and higher SPX histoscores compared to controls (TRPM2 and GPX4: p < 0.001, SPX: p < 0.001). Gender and age did not affect histoscores significantly. Conclusions Findings suggest TRPM2, GPX4, and SPX play roles in LP pathogenesis, indicating a need for further molecular studies to clarify their involvement. This contributes to understanding LP beyond the traditional apoptosis perspective.
Keywords: Lichen planus; Transient receptor potential melastatin-2; Glutathione peroxidase-4; Spexin